Conditional Cash Transfers to Incentivize Tuberculosis Screening: Description of a Novel Strategy for Contact Investigation in Rural South Africa. (2nd July 2021) - Baik, Yeonsoo; Hanrahan, Colleen F; Mmolawa, Lesego; Nonyane, Bareng A S; Albaugh, Nicholas W; Lebina, Limakatso; Siwelana, Tsundzukani; Martinson, Neil; Dowdy, David W
Abstract: Background: Providing incentives to screen close contacts for tuberculosis (TB) is an alternative to household-based contact investigation. We aimed to characterize patients and contexts where this incentive-based strategy might be preferred. Methods: This is a secondary analysis of a cluster randomized trial of TB contact investigation in Limpopo District, South Africa, conducted between 2016 and 2020. Twenty-eight clinics were randomly allocated to household-based vs incentive-based contact investigation. In the incentive-based arm, index participants and contacts received transport reimbursement and incentives for TB screening and microbiological diagnosis of contacts. We estimated differences in mean number of contacts per index participant with household-based vs incentive-based contact investigation overall and within subgroups of index participants. Results: A total of 3776 contacts (1903 in the incentive-based and 1873 in the household-based arm) were referred by 2501 index participants. A higher proportion of contacts in the incentive-based than household-based arm were adults (72% vs 59%), reported chronic TB symptoms (25% vs 16%) or ever smoking (23% vs 11%). Index participants who walked or bicycled to a clinic referred 1.03 more contacts per index (95% confidence interval [CI], .48 to 1.57) through incentive-based than household-based investigation. Index participants living with >5 household members referred 0.48 more contacts per index (95% CI, .03 to .94) through household-based than incentive-based investigation. Conclusions: Relative to household-based investigation, incentive-based investigation identifies contacts likely at higher risk for active TB. Incentive-based investigation may be more appropriate for index participants who can easily access clinics, versus household-based investigation for patients with large households. Clinical Trials Registration . NCT02808507. Abstract : Incentive-based contact investigation for tuberculosis is an alternative to household-based investigation that identifies a higher-risk group of contacts. Incentive-based contact investigation may be particularly appropriate for patients who do not require motorized transport to access clinics.